2014
DOI: 10.12688/f1000research.4263.1
|View full text |Cite
|
Sign up to set email alerts
|

Sub-strains of Drosophila Canton-S differ markedly in their locomotor behavior

Abstract: We collected five sub-strains of the standard laboratory wild-type Drosophila melanogaster Canton Special (CS) and analyzed their walking behavior in Buridan's paradigm using the CeTrAn software. According to twelve different aspects of their behavior, the sub-strains fit into three groups. The group separation appeared not to be correlated with the origin of the stocks. We conclude that founder effects but not laboratory selection likely influenced the gene pool of the sub-strains. The flies’ stripe fixation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 17 publications
(10 reference statements)
0
29
1
Order By: Relevance
“…Developmental nicotine exposure increased ethanol sedation in w B, but had no effect in EY5 flies at the nicotine and ethanol concentrations tested. Studies have shown that genetic background can have an effect on behaviors such as locomotion, sleep, and sensitivity to anesthetics [5153]. The contrasts we found are likely due to differences in genetic background.…”
Section: Resultscontrasting
confidence: 50%
“…Developmental nicotine exposure increased ethanol sedation in w B, but had no effect in EY5 flies at the nicotine and ethanol concentrations tested. Studies have shown that genetic background can have an effect on behaviors such as locomotion, sleep, and sensitivity to anesthetics [5153]. The contrasts we found are likely due to differences in genetic background.…”
Section: Resultscontrasting
confidence: 50%
“…8 Several studies have shown that genetic background has a strong effect on behavior in Drosophila, [9][10][11][12] and a common strategy to overcome this problem is to outcross mutations to the same genetic background. Yet, selection of which genetic background to use can itself be problematic, because these are likely to influence the behavioral phenotype being studied.…”
mentioning
confidence: 99%
“…Separate from updating reviews, there has been considerable discussion of methods for creating and managing 'living' systematic reviews that can extend their period of relevance by incorporating new research as it is published [74]. For example, a paper on Drosophila walking mechanisms published in the journal F1000 Research [75] employed the use of an updatable online figure that has been modified since publication to include more recent research [76]. There exist many significant challenges to establishing a living systematic review or systematic map.…”
Section: Knowledge Glutsmentioning
confidence: 99%